The Role of miRNAs in the Regulation of Pancreatic Cancer Stem Cells - Sabrina Bimonte; Antonio Barbieri; Maddalena Leongito; Giuseppe Palma; Vitale del Vecchio; Michela Falco; Raffaele Palaia; Vittorio Albino; Mauro Piccirillo; Alfonso Amore; Antonella Petrillo; Vincenza Granata; et al. (Hindawi Limited, 2016)
Pancreatic ductal adenocarcinoma is currently one of the deadliest cancers with low overall survival rate. This disease leads to an aggressive local invasion and early metastases and is poorly responsive to treatment with chemotherapy or chemoradiotherapy. Several studies have shown that pancreatic cancer stem cells (PCSCs) play different roles in the regulation of drug resistance and recurrence in pancreatic cancer. MicroRNA (miRNA), a class of newly emerging small noncoding RNAs, is involved in the modulation of several biological activities ranging from invasion to metastases development, as well as drug resistance of pancreatic cancer. In this review, we synthesize the latest findings on the role of miRNAs in regulating different biological properties of pancreatic cancer stem cells.